EXPLORING LITERARY TRADITION AND CREATIVE INFLUENCE ON THE UZBEK RING - Boboyev Yusuf Beknazarovich (American Journals Publishing, 2023)
Literary tradition serves as a powerful medium to transmit cultural values, historical perspectives, and creative influences across generations. This scientific article delves into the Uzbek literary tradition and examines its profound impact on fostering creativity within the Uzbek ring. By exploring the influences of classic Uzbek literature, this study aims to shed light on how literary traditions manifest in contemporary Uzbek literature, perpetuating creativity, and cultural preservation.